2014
DOI: 10.1177/1098612x14563098
|View full text |Cite
|
Sign up to set email alerts
|

Absence of bacterial DNA in culture-negative urine from cats with and without lower urinary tract disease

Abstract: A diagnosis of bacterial cystitis commonly relies on a positive microbiological culture demonstrating the presence of a significant number of colony-forming units/ml urine, as urine within the upper urinary tract, bladder and proximal urethra generally is considered sterile. Recent studies from human and veterinary medicine indicate the presence of non-culturable bacteria in culture-negative urine samples. The aim of the present study was to determine the occurrence of bacterial DNA in culture-negative urine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…26–30 In 2015, a study of bacterial DNA in culture-negative urine from cats with and without signs of FLUTD in Norway did not demonstrate the presence of unculturable bacteria as a common finding in either group of cats. 31 However, the sensitivity of the assays used may have precluded detection of very low levels of unculturable bacteria. 31…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…26–30 In 2015, a study of bacterial DNA in culture-negative urine from cats with and without signs of FLUTD in Norway did not demonstrate the presence of unculturable bacteria as a common finding in either group of cats. 31 However, the sensitivity of the assays used may have precluded detection of very low levels of unculturable bacteria. 31…”
Section: Discussionmentioning
confidence: 99%
“…31 However, the sensitivity of the assays used may have precluded detection of very low levels of unculturable bacteria. 31…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antimicrobial therapy: There is no evidence that occult bacterial infections play a role in FIC (Lund and others 2015) and one controlled study of the use of chloramphenicol showed no benefit (Barsanti and others 1982). …”
Section: Clinical Approachmentioning
confidence: 99%